Indonesian Exports to ASEAN: A Gravity Model Analysis of Primary and Manufactured Goods - Natanael, Yeremia (Pusat Pengembangan Kompetensi Aparatur Perdagangan, 2025)
This study aims to examine the relationship between Indonesian primary and manufactured exports to ASEAN member states and economic size and geographical distance and to explore the extent to which the standard and augmented gravity models explain these trade flows and whether the relationship differs between the two product categories. Using panel data on Indonesian exports to ASEAN members from 2013 to 2022, the results reveal a positive and significant relationship between the economic size of trade partners and Indonesian exports of primary and manufactured products, while geographical distance exhibits a negative and significant relationship. Landlocked status is negatively associated with exports of both product groups, whereas contiguity yields mixed results: positively related to primary exports but negatively attributed to manufactured goods exports. The findings corroborate the gravity model, confirming that economic size boosts Indonesian exports, while distance and landlocked status hinder trade, with contiguity benefiting primary exports but restricting manufactured goods trade. These results might pose policy implications, such that efforts to reduce transportation and logistic costs might contribute to a further increase in Indonesian exports to ASEAN members, particularly with relatively high income, such as Singapore, Malaysia, and Thailand, which are key markets in ASEAN for Indonesian exports. Moreover, Indonesia might need to improve logistics, enhance customs and trade administration efficiencies to reduce trade barriers, and improve accessibility, particularly for landlocked ASEAN members. Considering the adverse role of contiguity on manufactured product exports, Indonesia might benefit from enhanced industrial competitiveness through technological adoption, diversification into higher-technology products, and strengthening regional supply chain participation to align with ASEAN’s industrial demand structure.